Application of Brand Ambassador and Product Reviews to Improve Purchasing Decisions for Scarlett Whitening Products - Situmorang, Irvan Rolyesh (Outline Publisher, 2024)
The purpose of this research is to determine the influence of brand ambassadors and product reviews on purchase decisions for Scarlett Whitening Products, both partially and simultaneously. This research uses a quantitative methodology with a Likert scale for measurement. The population in this study cannot be known, so the sample collection uses the